Request releasing advance payment to purchase fire protection coating quantities for steel member surface - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request releasing advance payment to purchase fire protection coating quantities for steel member surface for BRACU new campus project.